Staff wellbeing in times of COVID-19. (November 2021) - Wong, Adrian; Olusanya, Olusegun; Parulekar, Prashant; Highfield, Julie
In the last 10 years, there has been increasing interest into the psychological wellbeing of healthcare providers. Within critical care, increasing attention is being paid to the concept of 'burnout' – a cluster of symptoms that adversely affect the health of critical care providers. Publications and statements from the major critical care societies have all addressed this syndrome and emphasised urgency in tackling it. The current COVID-19 pandemic has fundamentally changed the way we work, communicate and learn. Even before the pandemic, there have been growing concerns and acknowledgement that healthcare practitioners in intensive care are at increased risk of burnout and burnout syndrome. There has never been greater pressure on intensive care or indeed healthcare as a whole to look after so many patients during this pandemic and yet there is global acknowledgement that key to overcoming these challenges is to look after the care providers – both physically and psychologically. In this paper, we review the issue of burnout amongst healthcare practitioners during current pandemic. We present the impact of burnout on the individual and the system as a whole but perhaps most importantly, we provide a review of steps being taken to mitigate against these adverse outcomes in the short and longer term.